Fluency or Accuracy? EFL Teachers’ Evaluation of Google Translate and Digital Dictionaries in Classrooms - Zeli Utari; Veni Roza; Widya Syafitri (LPPM Universitas Advent Indonesia, 2026)
This study investigated the way in which EFL teachers perceived the quality of translations made by students using Google Translate and digital dictionaries in actual classroom situations. While previous studies on the use of such tools have not sufficiently addressed the issue of evaluation from the perspective of the teacher, this study adopted an explanatory sequential mixed methods design. In this study, 25 students performed translations using the two instruments, and their translations were rated by two EFL teachers based on a Likert-scale rubric on accuracy, fluency, and appropriacy. Results from the quantitative analysis showed that translation through digital dictionaries was rated higher compared to Google Translate with a mean difference of 4.84 (t(24) = -9.333, p < .001, d = 1.87, very large effect). Analysis of themes in the interviews shed light on this result since both teachers rated accuracy as the first factor and appropriateness and fluency as the second and third factors, respectively. Google Translate was used due to its ability to produce fluent translation and draft texts but not contextually appropriate and accurate. Unlike the digital dictionary, which promoted greater cognitive processing and careful consideration in word choice, an alternative strategy is suggested: the use of Google Translate to produce a first draft and then the digital dictionary to ensure correct word choice and accurate semantics prior to final submission.